Shear properties of C/C‐SiC sandwich structures - Heidenreich, Bernhard; Kraft, Harald; Bamsey, Nathan; Such‐Taboada, Miguel (International journal of applied ceramic technology, 2022)
Carbon fiber reinforced carbon‐silicon carbide (C/C‐SiC) sandwich structures have been developed using the Liquid Silicon Infiltration process and the in situ joining method. They offer high mass‐specific stiffness, low thermal expansion, and high environmental stability. Potential application areas are highly precise satellite structures, like optical benches. In this study, sandwich samples were manufactured using prepregs based on 2D carbon fibre fabrics and a phenolic resin precursor. Carbon fibre reinforced polymer preforms for folded and grid‐cores, as well as for the skin panels were manufactured using autoclave technique. In the second step, the sandwich components were pyrolyzed, leading to C/C preforms. For the build‐up of the sandwich samples, two skin panels were joined to a core structure and subsequently, the resulting C/C sandwich preform was siliconized. C/C‐SiC sandwich samples were tested under shear load. Shear strength, modulus, and fracture strain were determined and compared to the results obtained by analytical calculation. The shear properties were dependent on the fiber orientation in the core structure as well as on the core type and orientation. The sandwich shear stiffness obtained in the tests was close to the expected theoretical values, calculated on the basis of the material properties and the core geometry.